Preclinical rodent toxicity studies for long term use of ceftriaxone. (2015) - Ratti, Elena; Berry, James D.; Greenblatt, David J.; Loci, Lorena; Ellrodt, Amy Swartz; Shefner, Jeremy M.; Cudkowicz, Merit E.
Abstract: A 6-months rodent toxicology and pharmacokinetic (PK) study was performed to provide supportive safety data for long-term use of intravenous ceftriaxone in a clinical trial in patients with amyotrophic lateral sclerosis (ALS). Ceftriaxone was administered by subcutaneous injection at up to 2 g/kg/day to Sprague-Dawley Crl:CD (SD) rats. Ceftriaxone was found to be safe and well tolerated. Specifically, no significant differences in body weight and food consumption were observed between the treatment and control groups. With the exception of in red cell parameters decrease, there were no ceftriaxone-related changes in hematology, coagulation, clinical chemistry and urinalysis parameters. Injection site trauma and associated reversible anemia, likely due to chronic blood loss at the injection site, were all attributable to subcutaneous route of administration. Cecum dilatation and some skin changes were reversible after recovery period, while bile duct dilatation, observed only in a few animals, persisted. Changes in the non-glandular stomach do not have a human correlate. The no-observed-adverse-effect dose level (NOAEL) was 0.5 g/kg/day ceftriaxone in both sexes. Ceftriaxone showed rapid absorption with half-life values ranging between 1 and 1.5 h. Additionally, there was no evidence of accumulation and a virtually complete elimination by 16 h after the last dose. Overall there were no toxicologically meaningful drug-related animal findings associated with the long-term administration (6 months) of ceftriaxone. These results support safety of long-term use of ceftriaxone in human clinical trials.